Elliptic-Curve Cryptography Implementation on RISC-V Processors for Internet of Things Applications - Preethi Preethi; Mohammed Mujeer Ulla; G. Praveen Kumar Yadav; Kumar Sekhar Roy; Ruhul Amin Hazarika; Kuldeep Saxena K. (Journal of Engineering)
Elliptic-curve cryptography (ECC) is a popular technique of public-key cryptography used for secure communications in Internet of Things (IoT) applications. In this study, the implementation and analyze the Elliptic Curve Digital Signature Algorithm (ECDSA) with NIST-256 on MicroBlaze processors based on RISC-V architecture. This implementation aims to enhance secure communication and data exchange between IoT devices and also provides a detailed account of our ECDSA implementation on a RISC-V processor and evaluates its performance, achieving a reduction of 11.8% in execution time compared to existing techniques. The implementation takes 483 clock cycles and utilizes approximately 4096 bytes of memory. These results demonstrate that ECDSA can be efficiently implemented on RISC-V processors, making it a promising option for secure communication in IoT applications. Furthermore, the study highlights specific security considerations critical to implementing ECC on RISC-V processors, ensuring robust and reliable security in IoT environments.